Effects of the tide on the temporal and spatial physicochemical structure of the Kienké river estuary (South Atlantic Coast of Cameroon, Kribi) and its phytoplankton - Mama Anselme Crépin; Ghepdeu Gisele Flodore Youbouni; Fossi Tankoua Olivia; Bonga Manfred Desire; Abouga Bodo Willy Karol; Mandeng Thérésa Irma; Owona Edoa François Désiré; Tangko Noel Chuye; Ngoupayou Ndam Jules Rémi (Oceanological and Hydrobiological Studies)
The present work aimed to understand the physicochemical and phytoplanktonic structure of the Kienke estuary water in the urban area of Kribi town in relation to human activities and fluvial or oceanic influences. Field investigations and laboratory work were devoted to the sampling and measurement of some physicochemical and biological parameters, specific treatments and classical statistics (descriptive, multidimensional) of variables. Estuary water is characterised by an instability and spatio-temporal variations in its physicochemical parameters. The most sensitive parameters are as follows: a temperature ranging between 22.6°C and 31°C under the influence of atmospheric variations, electrical conductivity and salinity that are relatively high (0.22 < C. E < 49.70 mS cm−1; avg =16.56 mS cm−1; 0 < Sal < 29.32 PSU; avg = 11.51 PSU), and a pH that is overall acidic to basic (6 < pH < 8.86; avg = 7.75 ± 0.82). The nutrients variation (ammonium, nitrite, nitrate and orthophosphate) is very low in space and time, with a longitudinal distribution controlled by tidal flows, river flows and the biological pump. For the 64 samples collected, 167 phytoplankton taxa were identified. The most abundant (36.36%) were Chrysophyta Division, followed by Chlorophyta. Species richness is marked by brackish water taxa. According to this structure and the combination of both gradients, mineratilisation and organic matter enrichment is of a physicochemical typology, and the biotypology is hydrotypologically dependent.